Preindustrial-to-present-day changes in atmospheric carbon monoxide: agreement and gaps between ice archives and global model reconstructions - X. Faïn; S. Szopa; V. Naïk; P. Martinerie; D. M. Etheridge; D. M. Etheridge; R. H. Rhodes; C. M. Trudinger; C. M. Trudinger; V. V. Petrenko; K. Fourteau; P. Place; et al. (Atmospheric Chemistry and Physics)
Global chemistry–climate models (CCMs) play an important role in assessing the climate and air pollution implications of aerosols and chemically reactive gases. Evaluating these models under past conditions and constraining historical sources and sinks necessitate reliable records of atmospheric mixing ratios spanning preindustrial times. Such precious records were recently obtained for carbon monoxide (CO), documenting for the first time the evolution of this reactive compound over the industrial era. In this study, we compare the simulated atmospheric surface CO mixing ratios ([CO]) from two different sets of chemistry–climate models and emissions within the frameworks of CMIP5 and of CMIP6 (Coupled Model Intercomparison Project Phases 5 and 6) to recent bipolar ice archive reconstructions for the period spanning 1850 to the present. We analyse how historical (1850–2014) [CO] outputs from 16 ACCMIP (Atmospheric Chemistry and Climate Model Intercomparison Project) models and 7 AerChemMIP (Aerosol Chemistry Model Intercomparison Project) models over Greenland and Antarctica are able to capture both absolute values and trends recorded in multi-site ice archives. While most models underestimate [CO] at northern high latitudes, a reduction in this bias is observed between the ACCMIP and the AerChemMIP exercise. Over the 1980–2010 CE period (common era; all subsequent years in the paper are reported in CE), trends in ice archive and firn air observations and AerChemMIP outputs align remarkably well at northern and southern high latitudes, indicating improved quantification of anthropogenic CO emissions and the main CO sink (OH oxidation) compared to ACCMIP. From 1850 to 1980, AerChemMIP models and observations consistently show increasing [CO] in both the Northern Hemisphere (NH) and Southern Hemisphere (SH), suggesting a robust understanding of the CO budget evolution. However, a divergence in the [CO] growth rate emerges in the NH between models and observations over the 1920–1980 period, attributed to uncertainties in CO emission factors (EFs), particularly EFs for the RCO (residential, commercial, and other) and transportation sectors, although we cannot totally rule out the possibility that the CO record based on the Greenland ice archives may be biased high by CO chemical production processes occurring in the ice prior to the measurements (i.e. in situ CO production). In the Southern Hemisphere, AerChemMIP models simulate an increase in atmospheric [CO] from 1850 to 1980 that closely reproduces the observations (22 ± 10 ppb and 13 ± 7 ppb, respectively). Such agreement supports CMIP6 biomass burning CO emission inventories, which do not reveal a peak in CO emissions in the late 19th century. Furthermore, both SH models and observations reveal an accelerated growth rate in [CO] during 1945–1980 relative to 1850–1945, likely linked to increased anthropogenic transportation emissions.